A Study on Ancient Artifacts Around Badami Hill and Their Correlation with the Natural Rock Arch of Sidlaphadi. (28th June 2021) - Banerjee, Pradipta; Bajaj, Mayur
The Badami hill of Bagalkot district, Karnataka, India, houses a large rock arch termed "Sidlaphadi" that was used as a shelter by primitive man. The hill was searched to find any prehistoric artifact that would act as a directional marker towards the arch. An interesting structure was noted in one of the natural caves near the southwestern part of the hill at 15°55'06"N latitude and 75°41'02"E longitude. A miniature replica of the arch was carved onto the floor of the cave. The axis of the miniature bridge made an angle of 28.5 ± 1.5° with the 75°41'02"E longitude. The axis, upon extension eastwards at the defining angle reaches the northern slope of Sidlaphadi. The authors also located a megalithic stone arrangement in the northern part of the hill that had a pointed capstone and was thought to be oriented towards the rock arch. The stone arrangement was in the same latitude as that of the Sidlaphadi site, but the capstone was oriented 22°E towards the winter solstice sunrise at 112.5° azimuth.